2021
DOI: 10.1080/09537287.2021.1893405
|View full text |Cite
|
Sign up to set email alerts
|

Turning German automotive supply chains into sponsors for sustainability

Abstract: In recent decades, supply chains have become a critical source of competitive advantage. Yet, in the Germany automotive industry, supply chains have turned out to be untransparent and prone to sustainability breaches, with the recent Volkswagen manipulation scandal exemplifying the financial and reputational consequences. Many firms today, therefore, focus on what is called sustainable supply chain management (SSCM). While drivers, barriers, and performance implications of SSCM have been widely explored, littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…First, research has often identified so-called sustainability leaders among conventional, profit-oriented focal firms (e.g. Reuter et al, 2010;Wilhelm and Villena, 2021;Wissuwa and Durach, 2021). Our research suggests that there is likely a lot of ground to be covered beyond what these firms aim to achieve.…”
Section: Conclusion and Limitationsmentioning
confidence: 90%
See 1 more Smart Citation
“…First, research has often identified so-called sustainability leaders among conventional, profit-oriented focal firms (e.g. Reuter et al, 2010;Wilhelm and Villena, 2021;Wissuwa and Durach, 2021). Our research suggests that there is likely a lot of ground to be covered beyond what these firms aim to achieve.…”
Section: Conclusion and Limitationsmentioning
confidence: 90%
“…Reuter et al. , 2010; Wilhelm and Villena, 2021; Wissuwa and Durach, 2021). Our research suggests that there is likely a lot of ground to be covered beyond what these firms aim to achieve.…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…This work also contributes to the expanding corpus of FPR research in developing nations. GSCM and FPR research has often concentrated on developed nations such as Germany (Wissuwa and Durach 2023) and the UK (Esfahbodi et al 2023). Current GSCM researchers have transitioned to nations like India (Gedam et al 2023), China (Sheng et al 2022), Taiwan (Kuwornu et al 2023), etc., as an increasing number of companies relocate a substantial portion of their manufacturing companies to Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Supply chain management (SCM) is of utmost importance in the automobile sector. In the German there is a focus on sustainable supply chain management(SSCM) in automotive industry [1].Multiple businesses have done their best to maintain their strategic advantage by launching efficient, globally expansive supply networks [2].…”
Section: Introductionmentioning
confidence: 99%